Proton therapy of a pregnant patient with nasopharyngeal carcinoma. (July 2022) - Heimovaara, Joosje H.; Blommaert, Jeroen; Free, Jeffrey; Bolt, René A.; Gort, Elske M.; Depuydt, Tom; Boso Martinez, Cristina; Schoots, Mirthe H.; van Gerwen, Mathilde; van den Heuvel-Eibrink, Marry; Langendijk, Johannes A.; Schröder, Carolien P.; et al.
Highlights: First in human report of IMPT in a pregnant patient with nasopharyngeal carcinoma. Physical phantom measurements showed a thirty-fold decrease in fetal radiation dose when using IMPT compared to photon therapy. IMPT during pregnancy did not result in obstetrical or neonatal complications. Abstract: Background and purpose: Radiotherapy during pregnancy is rarely administered due to lack of data and practical challenges. This is the first detailed report of proton therapy as cancer treatment for a pregnant patient with nasopharyngeal carcinoma. Materials and methods: Pencil beam scanning proton therapy was prescribed to a pregnant patient to a total dose of 70 Gy (RBE) to the therapeutic CTV and 54.25 Gy to the prophylactic CTV, delivered in 35 fractions with a simultaneous integrated boost technique. Results: Phantom measurements showed a thirty-fold decrease in fetal radiation dose when using proton compared to photon therapy, with a total fetal dose of 5.5 mSv for the complete proton treatment, compared to 185 and 298 mSv for the photon treatment with and without lead shielding, respectively. After adminstering proton therapy during pregnancy, at 39 weeks of gestation, a healthy boy with a birthweight on the 83th percentile was delivered. Pediatric follow-up at 2 months of age of the offspring showed normal growth and age-adequate motor development with no signs of neurological problems. MR follow-up of the tumor 3 months after the end of treatment showed complete remission. Conclusion: This case demonstrates the potential of proton therapy for treatment during pregnancy. Compared to photon therapy, proton therapy can significantly limit fetal dose, while simultaneously offering a more optimized treatment to the patient.